Research of 1,3-oxazole-4-il-phosphonic acid derivative on the content of fatty acids of lipids in rats with arterial hypertension - Matskevych, Kateryna (ScienceRise: Pharmaceutical Science, 2018)
The number of patients with arterial hypertension (AH) continues to increase. Significant negative effects of arterial hypertension are structural, metabolic and functional disorders in the tissues of the myocardium, vessels and other organs, in particular, changes in the content of fatty acids (FA) and their correlation. The purpose of the study is to investigate the change in fatty acid composition of lipids in blood serum and tissues of rats with arterial hypertension under the influence of a new original compound, 1,3-oxazole-4-yl-phosphonic acid derivative (abbreviated name - oxazole derivative). Materials and methods. The studies were conducted on white, sexually mature rats. Arterial hypertension was modeled by salt load - salt drink (1 % solution of sodium chloride) with free access to it for 21 days. Animals from the 14th day received oxazole derivative at a dose of 25 mg / kg intraperitoneally, once daily, for 7 days. The content of fatty acids of centrifuged blood serum and homogenized in 0.9 % saline NaCl tissue was determined by gas chromatographic analysis. Results and discussion. The administration of oxazole derivative in the background of increased blood pressure in rats did not significantly affect the amount of SFA and USFA in serum in contrast to the group of rats with hypertension due to the tendency to restore the stearic acid content, but the changed content of linoleic and arachidonic acids practically did not differ from the values in the blank group. There was a restoration of the content of palmitic, stearic, linoleic and arachidonic acids in aorta. In heart, the change in the content of linoleic and arachidonic acids in the reverse direction compared with the blank group was established. Conclusions. The administration of 25 mg/kg (ED50) of oxazole derivative intravenous intraperitoneally once daily for 7 days with simultaneous simulation of arterial hypertension by salt load did not cause any adverse changes and led to the restoration of lipid parameters of SFA, USFA and PUFA